Emotional and behavioral problems, quality of life and metabolic control in NTBC-treated Tyrosinemia type 1 patients - Kimber van Vliet; Willem G. van Ginkel; Rianne Jahja; Anne Daly; Anita MacDonald; Corinne De Laet; Roshni Vara; Yusof Rahman; David Cassiman; Francois Eyskens; Corrie Timmer; Nicky Mumford; et al. (Orphanet Journal of Rare Diseases, 2019)
Abstract Background Treatment with 2-(2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione (NTBC) and dietary phenylalanine and tyrosine restriction improves physical health and life expectancy in Tyrosinemia type 1 (TT1). However, neurocognitive outcome is suboptimal. This study aimed to investigate behavior problems and health-related quality of life (HR-QoL) in NTBC-dietary-treated TT1 and to relate this to phenylalanine and tyrosine concentrations. Results Thirty-one TT1 patients (19 males; mean age 13.9 ± 5.3 years) were included in this study. Emotional and behavioral problems, as measured by the Achenbach System of Empirically Based Assessment, were present in almost all domains. Attention and thought problems were particularly evident. HR-QoL was assessed by the TNO AZL Children’s and Adults QoL questionnaires. Poorer HR-QoL as compared to reference populations was observed for the domains: independent daily functioning, cognitive functioning and school performance, social contacts, motor functioning, and vitality. Both internalizing and externalizing behavior problems were associated with low phenylalanine (and associated lower tyrosine) concentrations during the first year of life. In contrast, high tyrosine (and associated higher phenylalanine) concentrations during life and specifically the last year before testing were associated with more internalizing behavior and/or HR-QoL problems. Conclusions TT1 patients showed several behavior problems and a lower HR-QoL. Associations with metabolic control differed for different age periods. This suggests the need for continuous fine-tuning and monitoring of dietary treatment to keep phenylalanine and tyrosine concentrations within target ranges in NTBC-treated TT1 patients.